Implikasi tafsiran Muhammad Asad bagi perkataan ‘Islam’ terhadap pegangan Ahl al-Sunnah wa al-Jamaah - Nurhayati Abdullah,; Kamarudin Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Islam is the name of religion promulgated by the Prophet Muhammad (pbuh). Islam has its own specific shariah that distinguishes it from other religions. Based on Quranic reference, the scholars have understood that the only religion that is true and acceptable by Allah is Islam. With regard to Muhammad Asad nonetheless, he has interpreted ‘Islam’ differently from the interpretation of mu’tabar. Muhammad Asad interpreted ‘Islam’ as a self-surrender to God with generic language meaning. This study attempts to see the premise of his interpretation which differs from the interpretation of mainstream Muslims. This paper also seeks to investigate the implication of such interpretation to the belief of Ahl al-Sunnah wa al-Jamaah. This study using content analysis method thematically on his work of tafseer, “The Message of the Quran” by selecting texts from the Quran that contain the word ‘Islam’ and semantically towards some conceptual texts that are related to it and relevant to the religious pluralism issue. The study finds that Muhammad Asad's interpretation in line with liberal approach and contradicts the Ahl al-Sunnah wa al-Jamaah’s tenets by accepting and recognizing the truth of other religions that end with inclusivism and religious pluralism.